2020
DOI: 10.3389/fmolb.2020.606779
|View full text |Cite
|
Sign up to set email alerts
|

SARS CoV-2 Organotropism Associated Pathogenic Relationship of Gut-Brain Axis and Illness

Abstract: COVID-19 has resulted in a pandemic after its first appearance in a pneumonia patient in China in early December 2019. As per WHO, this global outbreak of novel COVID-19 has resulted in 28,329,790 laboratory-confirmed cases and 911,877 deaths which have been reported from 210 countries as on 12th Sep 2020. The major symptoms at the beginning of COVID-19 are fever (98%), tussis (76%), sore throat (17%), rhinorrhea (2%), chest pain (2%), and myalgia or fatigue (44%). Furthermore, acute respiratory distress syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 75 publications
0
17
0
4
Order By: Relevance
“…Investigations of SARS-CoV-2 organotropism, its duration in the target organs and the correlation with disease progression are pivotal for developing effective strategies for the containment of the pandemic. Some studies revealed SARS-CoV-2 distribution in human tissues and viral shedding in body fluids, 18,[35][36][37][38] but the translational significance remains unclear. Our pathological evidence of SARS-CoV-2 presence in late stage of critically ill patients with COVID-19 suggests that continued usage of antiviral therapy is indispensable throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of SARS-CoV-2 organotropism, its duration in the target organs and the correlation with disease progression are pivotal for developing effective strategies for the containment of the pandemic. Some studies revealed SARS-CoV-2 distribution in human tissues and viral shedding in body fluids, 18,[35][36][37][38] but the translational significance remains unclear. Our pathological evidence of SARS-CoV-2 presence in late stage of critically ill patients with COVID-19 suggests that continued usage of antiviral therapy is indispensable throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have revealed that SARS-CoV-2 infection can alter the intestinal microbiota in COVID-19 patients, characterized by the enrichment of pathogenic microbes and opportunistic pathogens, resulting in gut dysbiosis[ 100 - 105 ]. As described previously, the absorption of tryptophan is associated with neurological abnormities, as it is the precursor for the synthesis of 5-hydroxytryptophan in the brain[ 103 ]. It also regulates the levels of antimicrobial peptides that affect the composition of the gut microbiota, leading to increased sensitivity to intestinal inflammation and epithelial dysfunction[ 106 ].…”
Section: Mechanisms Of Gi Tract Involvementmentioning
confidence: 99%
“…It also regulates the levels of antimicrobial peptides that affect the composition of the gut microbiota, leading to increased sensitivity to intestinal inflammation and epithelial dysfunction[ 106 ]. Thus, this viral infection might affect the homeostasis of the gut-brain axis through the intestinal microbiota[ 103 , 107 ]. However, further investigations are needed to clarify whether the dysbiosis is specific to SARS-CoV-2 infection or a consequence of critical illness.…”
Section: Mechanisms Of Gi Tract Involvementmentioning
confidence: 99%
“…The human intestinal tract, the niche of a large number of intestinal microflora, is mainly dominated by Firmicutes and Bacteroides, which produce a variety of metabolites to maintain intestinal homeostasis (Foster and McVey Neufeld, 2013). Intestinal microflora can affect immune functions such as the production of acetate and butyrate and protection from respiratory virus infection; changes in the intestinal microflora may induce behavioral changes, leading to depression and confusion (Dinan et al, 2015;Dhar and Mohanty, 2020;Shinu et al, 2020).…”
Section: Intestinal Flora Imbalancementioning
confidence: 99%